1985
DOI: 10.2307/280320
|View full text |Cite
|
Sign up to set email alerts
|

Human Behavior, Demography, and Paleoenvironment on the Colorado Plateaus

Abstract: Archaeological and paleoenvironmental data are integrated in an investigation of culture change among the Anasazi of the American Southwest by a conceptual model of the interaction among environment, population, and behavior, the major determinants of human adaptive systems. Geological, palynological, and dendrochronological reconstructions of low and high frequency environmental variability coupled with population trends are used to specify periods of regional population-resource stress that should have elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 16 publications
5
126
1
Order By: Relevance
“…For example, cases of inter-community exchange, and geographically diversified mutual insurance arrangements are well-documented in the historical, anthropological and economic literature (Kirkby, 1974;Dean et al, 1985;Halstead and O'Shea, 1989;Platteau, 2000). However, the creation and maintenance of socio-economic connections over larger areas would have entailed higher costs since incentive and information problems would be more severe among geographically distant individuals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cases of inter-community exchange, and geographically diversified mutual insurance arrangements are well-documented in the historical, anthropological and economic literature (Kirkby, 1974;Dean et al, 1985;Halstead and O'Shea, 1989;Platteau, 2000). However, the creation and maintenance of socio-economic connections over larger areas would have entailed higher costs since incentive and information problems would be more severe among geographically distant individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the tree-ring study of Fritts et al (1965) who found that the Great Drought was associated with reduced winter and summer precipitation and elevated summer and autumn temperatures. The middle-12th and late-13th century droughts occurred after population expansions, during a time when people were living at the limit of their environmental and agricultural support systems (Dean et al, 1985;Dean, 1988). Some of the droughts Figure 10.…”
Section: Drought and Its Relation To The Pacific Decadal And Atlanticmentioning
confidence: 99%
“…Its bounded topography combined with the rich paleoenvironmental record permits the creation in the computer of a dynamic resource landscape that accurately replicates actual conditions in the valley from A.D. 200 to 1500. Low-and high-frequency variations in alluvial hydrologic and depositional conditions, effective moisture, and climate have been reconstructed in unprecedented detail with dendroclimatology, surficial geomorphology, palynology, and archaeology (11)(12). High-frequency climatic variability is represented by annual June Palmer Drought Severity Indices (PDSI), which reflect the effects of meteorological drought (moisture and temperature) on crop production (13).…”
mentioning
confidence: 99%